2010
DOI: 10.1017/s0950268809991567
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistantStaphylococcus aureus(MRSA) in food production animals

Abstract: SummaryUntil recently, reports on MRSA in livestock were mainly limited to occasional detections in dairy cattle mastitis. Since 2005 however, studies show the existence of an MRSA clone, CC398, which has been reported colonizing pigs, veal calves and broiler chickens and infecting dairy cows. Many aspects of its prevalence in pigs are not yet understood. In other livestock, colonizing capacity and reservoir status are still unclear.. MRSA CC398 has also been detected in meat but, like for other MRSA, the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
168
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(182 citation statements)
references
References 184 publications
8
168
1
3
Order By: Relevance
“…aureus in bovine mastitis milk. The presence of these staphylococci in milk is a growing problem in veterinary medicine not only limiting antimicrobial treatment options, but also representing a burden for public health (Walther and Perreten, 2007;Vanderhaeghen et al, 2010;Holmes and Zadoks, 2011;Zadoks et al, 2011). Methicillin-resistant Staph.…”
Section: Discussionmentioning
confidence: 99%
“…aureus in bovine mastitis milk. The presence of these staphylococci in milk is a growing problem in veterinary medicine not only limiting antimicrobial treatment options, but also representing a burden for public health (Walther and Perreten, 2007;Vanderhaeghen et al, 2010;Holmes and Zadoks, 2011;Zadoks et al, 2011). Methicillin-resistant Staph.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated MRSA in raw chicken meat (Kitai et al, 2005;Lee, 2006;Dohoo et al, 2009) and broilers at slaughterhouses (Mulders et al, 2010). LA-MRSA isolates in poultry have previously been found in the Netherlands (Leenders et al, 2007;Geenen et al, 2012) and Belgium (Nemati et al, 2008;Persoons et al, 2009;Vanderhaeghen et al, 2010a;Pletincks et al, 2011). However, these studies were rather limited and different isolation methods were used.…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) strains are an important cause of hospital-acquired and community-acquired infections worldwide (Stewart & Holt, 1963;von Eiff et al, 2001;Kluytmans-VandenBergh & Kluytmans, 2006). However, MRSA strains are no longer confined to healthcare settings, and are also a growing problem in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Specific studies are needed to examine the incidence of MRSA in foods and the environments of food producing facilities in order to evaluate the relative risk of foods as sources of infection in humans. So far, MRSA have been isolated from food producing animals (Vanderhaegen et al 2010) and foods of animal origin, such as meat products from cattle and pigs (van Loo et al 2007), milk and dairy products (Normanno et al 2007). MRSA has been associated with food both through contamination from humans (Kluytmans et al 1995) and due to the colonisation of food-producing animals (Voedsel en Waren Autoriteit 2007).…”
mentioning
confidence: 99%